+0  
 
0
54
1
avatar+316 

 

 

steps to solve please?

cerenetie  Aug 14, 2018
 #1
avatar+88775 
+1

3x + y  = 4     (1)

2x + y  = 7       multiply this through  by -1 ⇒  -2x - y  = -7   (2)

 

Add (1) and (2)   ⇒  x  = -3

Subbing into  either equation to  find y  we get  3 (-3) + y  = 4 ⇒  -9 + y  = 4  add 9 to  both sides  y   = 13

(-3, 13)  is the solution 

 

-2x + 6y  = -38       multiply  through by  3 ⇒   -6x + 18y  = -114    (1)

3x - 4y  = 32           multiply through  by 2 ⇒   6x - 8y  = 64   (2)

 

Add (1) and (2) ⇒  10y  = -50    ⇒ divide through by 10 ⇒  y  = - 5

Subbing this back into the first equation to find  x, we get  -2x + 6(-5)  = -38   

-2x - 30  = -38

Add 30 to   both sides  -2x  = -8

Divide both sides by -2

x  = 4

 

(4, -5)  is the solution     

 

Last one

x + 3y - z  = 6     (1)

4x - 2y + 2z  = -10    divide through by 2 ⇒    2x - y + z  = -5       (2)

6x + z  = -12  ⇒    z  = -12 - 6x   (3)

 

Sub (3)  into (1) and  (2)  for  z

 

x + 3y - [ -12 - 6x] = 6 ⇒    x + 3y + 12 + 6x  = 6 ⇒  7x + 3y  = -6    (4)

2x - y + [ -12 - 6x] = -5 ⇒   2x - y - 12 - 6x  = -5  ⇒ -4x - y = 7  mulltiply through by 3 ⇒

-12x - 3y  = 21  ( 5)

 

Add (4)  and (5)

-5x  = 15      divide through by -5

x  = -3

Using (4)  we can  find y ⇒  7(-3) + 3y  = -6  ⇒  -21 + 3y = -6 ⇒  3y = 15 ⇒ y = 5

Using (3) we can find z ⇒  z = -12 -6(-3) ⇒  z = -12 + 18 ⇒  z  = 6

 

So...the solution is  (-3, 5, 6)

 

 

cool cool cool

CPhill  Aug 14, 2018

26 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.